Value creation drivers in SOA for research & innovation: A proposed framework for HEI context - Golooba, Moses; Ahlan, Abdul Rahman (2013)
Currently, higher education institutions (HEIs) are looking for new ways of collaborating to share specialized competences (knowledge & skills) both internally and externally. This is aimed at improving their business processes as well as increasing their productivity. Value co-creation (VCC) is an effective model to improve the way organizations collaborate and share resources. VCC is a concept that defines how products or services can be collaboratively created between the firm, its customers, partners and other stakeholders. However, there is insufficient research on how value can be co-created within the HEIs context. Hence the aim of this study is to examine the concept of value co-creation in the context of research collaboration in HEIs. The main objective of this study will be addressed through answering the following research question: How can ICT be an enabler of value co-creation within the context of HEIs. Drawing from the theory of service dominant logic (SDL) and the work systems theory (WST), we posit that; using a service-oriented enterprise architecture (SOEA) as an enabler, HEIs can co-create value between themselves through six key value drivers i.e.; connectivity, automation, agility, service interactions, intelligence, and resource integration. This extends Ching et al, [1] model on the co-creation dynamics in B2B environments.